Impact of metabolic syndrome on patient outcomes of supination-external rotation ankle fracture. Issue 7 (July 2019) - Park, Young Hwan; Kim, Woon; Park, Ji Hun; Kim, Hak Jun
Highlights: Patients with metabolic syndrome are at risk for worse clinical outcomes than patients without metabolic syndrome after surgical treatment of ankle fractures. Metabolic syndrome should be treated together with surgical treatment of ankle fractures. Progression of posttraumatic arthritis was not different between two groups, but long-term follow-up is needed to make a definite conclusion. Abstract: Metabolic syndrome has been known as a risk factor for morbidity following orthopedic procedures, yet its impact on surgical treatment of ankle fractures remains unclear. The aim of this study was to compare the patient outcomes of surgical treatment of supination-external rotation ankle fractures in patients with and without metabolic syndrome. This study was designed as a retrospective matched case-control study. Forty-nine patients with supination-external rotation ankle fracture and metabolic syndrome were age-, sex-, and fracture type-matched with 49 controls without metabolic syndrome. Olerud-Molander Ankle Score (OMAS), Visual Analog Scale (VAS), Kellgren and Lawrence (K&L) scale, and complications were assessed at final follow-up. The mean postoperative follow-up was 19.5 months (range, 13–44). The OMAS measurements in the metabolic syndrome group were lower than those in the control group (p = 0.006) and the VAS for pain measurements in the metabolic syndrome group were greater than those in the control group (p < 0.001). The K&L scale and complications did not differ significantly between the two groups. Patients with metabolic syndrome are at risk for higher pain scores and lower functional outcomes after surgical treatment for supination-external rotation ankle fracture. These results suggest that metabolic syndrome should be treated together with ankle fractures.